Tartaric stabilization of Rosé wine by ion exchange resins: impact on phenolic and sensory profile - Cosme, Fernanda (2019)
Wine tartaric stabilization is essential to satisfy the wine quality criteria, and consequently the consumer’s acceptance. Several techniques are available to prevent tartaric precipitation (potassium hydrogen tartrate and calcium tartrate) in wine. Beside the addition of enological products, the use of ion exchange resins is also an acceptable technique for wine tartaric stabilization by the OIV (OIV, 2016). However, according to our knowledge, there are no studies in Rose wine concerning ionexchange resins for tartaric stabilization. Furthermore, Rose wine consumption shows an increase in consumption trend in the last years (between 2008 and 2014), representing nowadays near 10% of the world wine production. Therefore, the aim of this study was to evaluate the effect of ion exchange resins on wine tartaric stabilization efficiency and the impact on wine quality, compared to the effect of the addition of conventional enological additives. For this objective, a Rose wine from the Douro Valley, vintage 2015, was used. The experimental design was developed in a winery at a semiindustrial scale. After wine treatments tartaric stability was measured by the mini contact test. In order to, understand the impact of the treatments on Rose wine quality, wines phenolic composition - total phenols, flavonoid and non-flavonoid compounds as well as the chromatic characteristics by the CIELab method were also evaluated. Finally, wine sensory analysis was performed by a panel composed by seven trained panelists. As expected, the treatments stabilized the wine against tartaric precipitation. Also, results so far obtained showed, that in general, the use of ion exchange resins impacted mainly in the color of Rose wine. In addition, decrease in color intensity was also observed by sensory panel, but wine treatment with ion exchange resins was further scored for attributes usually appreciate by wine consumers, like limpidity and fruit aroma, and less scored for astringency. These results suggested that ion exchange resins could be an alternative to conventional enological additives to prevent Rose tartaric stabilization.